Life as a Sacrificial Offering. Environmental Degradation and Suffering in the Copiapó-Tierra Amarilla Conurbation, Chile - Duarte Hidalgo, Cory (2025)
The Copiapó-Tierra Amarilla conurbation is a sacrificial territory in which there is an environmental crisis derived from bad development, in which environmental degradation and suffering are prioritized over the life of people and ecosystems. The main objective of this research was to understand the sacrificial practices deployed by the women of Copiapó and Tierra Amarilla regarding the sacrifice of life in contexts of environmental degradation and suffering. The study is qualitative in nature and resorts to a narrative design, focused on a case study, in which narrative interviews are applied to 28 different women, social leaders of Copiapó and Tierra Amarilla in a fieldwork conducted in its first phase in 2019 and in a second phase in 2024. As a result, it is observed that women deploy sacrificial practices and habituation to environmental degradation and suffering, however, they show resistance and critical positions in front of the sacrifice of life in Atacama. The narratives allow us to identify a sacrificial structure installed since the 19th century and which is currently expressed in the constant offering of the lives of those who inhabit the territory, generating sacrificial practices in women, tending to habituation, but also incipient processes of resistance and defense of life.